Multiple tyrosine residues in the cytosolic domain of the erythropoietin receptor promote activation of STAT5. - Klingmüller, U (1996)
Signaling through the erythropoietin receptor (EPO-R) is crucial for proliferation, differentiation, and survival of erythroid progenitor cells. EPO induces homodimerization of the EPO-R, triggering activation of the receptor-associated kinase JAK2 and activation of STAT5. By mutating the eight tyrosine residues in the cytosolic domain of the EPO-R, we show that either Y343 or Y401 is sufficient to mediate maximal activation of STAT5; tyrosine residues Y429 and Y431 can partially activate STAT5. Comparison of the sequences surrounding these tyrosines reveals YXXL as the probable motif specifying recruitment of STAT5 to the EPO-R. Expression of a mutant EPO-R lacking all eight tyrosine residues in the cytosolic domain supported a low but detectable level of EPO-induced STAT5 activation, indicating the existence of an alternative pathway for STAT5 activation independent of any tyrosine in the EPO-R. The kinetics of STAT5 activation and inactivation were the same, regardless of which tyrosine residue in the EPO-R mediated its activation or whether the alternative pathway was used. The ability of mutant EPO-Rs to activate STAT5 did not directly correlate with their mitogenic potential.